EVALUATION OF VARIANT SOLUTIONS AND METHODS OF RAILWAY ROUTE OPTIMIZATION - Zafirovski Zlatko; Jasovic Andzela (My University, 2021)
In this research, the concept of evaluation of a variant solution is explained and a brief overview of optimization methods. The evaluation criteria are explained in detail: minimum investment, minimum maintenance and investment costs, maximum quality of service and minimum environmental impact.
Keywords: evaluation of variant solutions, optimization methods, criterion functions for evaluating a variant solution.